Clinical usefulness of a novel fluorescence technique for the intraoperative diagnosis of surgical margins in patients with breast cancer. Issue 10 (24th August 2021) - Ueo, H; Ueo, H; Minoura, I; Gamachi, A; Doi, T; Yamaguchi, M; Yamashita, T; Tsuda, H; Moriya, T; Yamaguchi, R; Kozuka, Y; Sasaki, T; et al.
Abstract : In both 5- and 15-min data, FI was significantly higher in malignant tissues than in benign tissues. The diagnostic accuracy was similar at 5 and 15 min. Therefore, the 5-min FI was enough applying in the further analyses.